sendo f(x)= 4x⁴-2x e g(x)= x²-2x+6. Calcule f(x)g(x).
Soluções para a tarefa
Respondido por
0
Resposta:
Explicação passo a passo:
.
. Multiplicação de polinômios
.
f(x).g(x) = (4x^4 - 2x) . (x²- 2x + 6)
. = 4x^4 . x² + 4x^4 . (- 2x) + 4x^4 . 6 - 2x . x² - 2x . (- 2x) - 2x . 6
. = 4x^6 - 8x^5 + 24x^4 - 2x^3 + 4x² - 12x
.
(Espero ter colaborado)
Perguntas interessantes
Português,
7 meses atrás
Física,
7 meses atrás
Português,
7 meses atrás
Química,
7 meses atrás
Português,
7 meses atrás
Ed. Física,
1 ano atrás
Biologia,
1 ano atrás
Ed. Física,
1 ano atrás